Function-based Feasibility Study and Benchmark for MID Concepts. (2016) - Jürgenhake, Christoph; Falkowski, Tommy; Fechtelpeter, Christian; Dumitrescu, Roman
Abstract: Molded Interconnect Devices (MID) are three-dimensional structures with integrated electronic circuit traces that facilitate the miniaturization and functional integration of technical products. This opens up new possibilities for the conception and design of products but also comes with specific challenges. The complexity of MIDs has a major influence on the design process of the product and the design of the associated manufacturing system. There are a large number of available MID manufacturing processes composed of various steps, each one with specific advantages and constraints attached to them. As a result, the manufacturing process has to be taken into consideration at an early stage of the product development cycle. A systematic design approach is therefore necessary in order to successfully create a feasible product using MID technology. This paper presents the first part of a procedure that enables a systematic conception of MIDs and the associated manufacturing system while taking product functions into account, starting with a feasibility study for MID concepts.